How Tertiary EFL Learners Dealt with Problems in Oral Communication in the Target Language - Tono Suwartono, Wijiasih Eka Pertiwi, Nurhayati (International Journal of Advanced Science and Technology, 2020)
Speaking is an important skill because through speaking people convey direct ideas or messages orally to others in life. In speaking skills some components, namely pronunciation, grammar, vocabulary, and intelligibility determine communication success and fluency. In the context of EFL learning, many students find it difficult to speak in English. Difficulty in speaking English is also experienced by learners at higher education. Nevertheless, the difficulties in speaking English can be overcome with particular strategy use. This research was conducted to examine the problems facing the tertiary EFL learners in speaking English as the target language and identify the strategies used in their oral communication. The study involved seventy-eight students at the fourth semester in the Department of English Language Teaching at Universitas Muhammadiyah Purwokerto that were randomly chosen as samples. Data on learning strategies were identified and classified according to Oxford (1990)’s Strategy Inventory for Language Learning (SILL) which classifies strategies into two: direct strategies consisting of memory, cognitive, and compensation strategies and indirect strategies comprising affective, metacognitive and social strategies. Findings indicated that many students had more than one speaking difficulties. The difficulties covered: (1) linguistic factors, which included lack of vocabulary (55.93%), grammar (51.9%), pronunciation (25.6%), (2) psychological factors, which included lack of motivation (55.8%), fear of making mistakes (52.6%), anxiety (49.35%), lack of confidence (43.6%), and shyness (34.6%). In order to overcome those problems, students applied some strategies. Findings indicated that the strategies used the most were affective strategies (67.53%), then memory strategies (67.25%), compensation strategies (64.93%), cognitive strategies (61.53%), social strategies (59.8%), metacognitive strategies (56.4%).